2021
DOI: 10.3390/biology10100981
|View full text |Cite
|
Sign up to set email alerts
|

Disease Modeling of Mitochondrial Cardiomyopathy Using Patient-Specific Induced Pluripotent Stem Cells

Abstract: Mitochondrial cardiomyopathy (MCM) is characterized as an oxidative phosphorylation disorder of the heart. More than 100 genetic variants in nuclear or mitochondrial DNA have been associated with MCM. However, the underlying molecular mechanisms linking genetic variants to MCM are not fully understood due to the lack of appropriate cellular and animal models. Patient-specific induced pluripotent stem cell (iPSC)-derived cardiomyocytes (iPSC-CMs) provide an attractive experimental platform for modeling cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 199 publications
(223 reference statements)
0
4
0
Order By: Relevance
“…A recent threedimensional electron microscopy study revealed different mitochondrial networks, morphology and interactions with other cellular components compared to the other muscles, implying that the energy demand regulates mitochondria [152]. The decreased mitochondrial function causes cardiac dysfunction and leads to cardiomyopathy with sarcomere disarray, suggestive of mitochondrial involvement in sarcomere organization or homeostasis [153][154][155].…”
Section: (A) Mitochondriamentioning
confidence: 99%
“…A recent threedimensional electron microscopy study revealed different mitochondrial networks, morphology and interactions with other cellular components compared to the other muscles, implying that the energy demand regulates mitochondria [152]. The decreased mitochondrial function causes cardiac dysfunction and leads to cardiomyopathy with sarcomere disarray, suggestive of mitochondrial involvement in sarcomere organization or homeostasis [153][154][155].…”
Section: (A) Mitochondriamentioning
confidence: 99%
“…Overall, changes in cell structure or shape, such as hypertrophy, could be a more successful target for in vitro disease models [ 61 ]. Mitochondrial hypertrophy disease models established from patient iPSC-CMs have also been recently reviewed [ 62 ].…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 99%
“…Mitochondrial diseases (MDs) are rare, with a prevalence of 5–12/100,000 ( 1 ). They are characterized by oxidative phosphorylation (OXPHOS) dysfunction caused by nuclear and/or mitochondrial DNA (mtDNA) variations ( 2 4 ). Approximately 20–40% of children with MDs develop cardiac manifestations, such as hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM), arrhythmias, left ventricular non-compaction (LVNC), heart failure and sudden cardiac death ( 5 – 8 ), which are termed mitochondrial cardiomyopathy (MCM) ( 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by oxidative phosphorylation (OXPHOS) dysfunction caused by nuclear and/or mitochondrial DNA (mtDNA) variations ( 2 4 ). Approximately 20–40% of children with MDs develop cardiac manifestations, such as hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM), arrhythmias, left ventricular non-compaction (LVNC), heart failure and sudden cardiac death ( 5 – 8 ), which are termed mitochondrial cardiomyopathy (MCM) ( 2 , 4 ). Combined oxidative phosphorylation deficiency-31 (COXPD31) (OMIM: 617228) is an autosomal recessive mitochondrial disease caused by mutations in the MIPEP gene.…”
Section: Introductionmentioning
confidence: 99%